Drain and Debulk: A Dual Approach to Advanced Lower Limb Lymphedema Using Simultaneous LVB and Lymph-Sparing Liposuction - Aditya Wicaksana; Mohamad Rachadian Ramadan; Parintosa Atmodiwirjo (Jurnal Plastik Rekonstruksi, 2025)
Background: Advanced-stage lymphedema is characterized by lymphatic dysfunction and fibroadipose overgrowth. Single-modality treatments, such as lymphaticovenous bypass (LVB) or liposuction alone, are often inadequate. This case series evaluates the safety and outcomes of simultaneous LVB and lymph-sparing liposuction in advanced lower-limb disease.Method: We conducted a case series involving four patients (n=4) with secondary lower limb lymphedema (ISL stage II–III; LDB stage IV–V). All underwent simultaneous LVB and lymph-sparing liposuction. Limb volume was calculated using the truncated cone formula at baseline, 1 week, and 12 months postoperatively. Quality of life was measured using the LYMPH-Q questionnaire. One patient with bilateral lymphedema received LVB on both limbs but underwent liposuction on only one, allowing for direct internal comparison.Results: In all four patients patients demonstrated immediate postoperative limb volume reductions ranging from 12.13% to 37.68%, with further improvements at 12 months (up to 42.1%). Quality of life scores significantly increased, with improvements of up to 37.29%. In the bilateral case, the limb treated with both LVB and liposuction showed superior outcomes compared to the limb treated with LVB alone. No major complications occurred.Conclusions: Simultaneous LVB and lymph-sparing liposuction is a safe and effective treatment for advanced lymphedema. This dual-modality approach addresses both fluid accumulation and fibrotic hypertrophy, resulting in better functional and aesthetic outcomes than either technique alone. Larger studies with longer follow-up are needed to confirm these findings and optimize patient selection.